The association between music training and executive function in 6–7-year-old children - Bayanova, Larisa; Chichinina, Elena; Aslanova, Margarita (Frontiers in Education, 2024)
Executive function development is especially important in the last year of the preschool period because this period precedes the transition to school. Therefore, it is relevant to study extracurricular activities that can positively impact the development of executive function in 6-7-year-old children. According to earlier research, executive function development might be positively influenced by music training. The current cross-sectional study aimed to explore differences in executive function among 6-7-year-old preschoolers depending on participation in music training. In the current research, children were divided into two groups of 37 participants each: children who received music training for at least half a year and children who did not receive music training. Children in both groups did not participate in dance training because music is also actively used during dance training. Background variables such as participation in extracurricular activities, screen time, family singing activities, maternal education, and family income level did not differ between the groups. The study revealed that the children who received music training had a higher level of motor inhibitory control compared to the children who did not receive music or dance training. This study offers further support for the association between executive function and music training in preschoolers.